Heavy metal induced resistance to herbivore of invasive plant: implications from inter- and intraspecific comparisons - Zhou, Yue; Chen, Chao; Xiong, Yuntao; Xiao, Feng; Wang, Yi (Frontiers in Plant Science, 2023)
Heavy metals can affect the content of secondary metabolites in plants, which are one of the important defenses of plants against herbivores. However, studies on the effects of heavy metals on secondary metabolites of invasive plants are scarce. Phytolacca americana is an invasive plant in China, which can hyperaccumulate the heavy metal Mn. This study used two Mn treatments (control and treatment group) and four species from Phytolacca (including the native and introduced populations of P. americana, its native and exotic congeners in China) to investigate the impact of heavy metal Mn on the invasive ability of P. americana. The results show that heavy metal Mn can enhance the inhibitory effect of the introduced populations of P. americana on the growth of herbivore (the weight of herbivore has decreased by 66%), and altered the feeding preferences of herbivore. We also found that heavy metal Mn can significantly increase the content of quantitative resistance in the leaves of the introduced populations of P. americana and is higher than its native populations, native and exotic congeners. In addition, heavy metal Mn caused the quantitative resistance of the exotic congener significantly higher than that of the native congeners. In summary, the heavy metal Mn can increase the content of secondary metabolites in leaves to enhance the interspecific competitive advantage of P. americana and promote its invasion, and also increase the invasion risk of exotic species.